Potential impacts of COVID-19 research on livestock health research and innovation - Nene, Vishvanath M. (2021)
POLICY SEMINAR Virtual Event - Building back better: How can public food and agricultural research institutions be strengthened and rebuilt after the COVID-19 pandemic? Co-Organized by IFPRI and the International Consortium on Applied Bioeconomic Research (ICABR) FEB 2, 2021 - 09:30 AM TO 11:00 AM EST